The problem of distance in the theoretical thought of Sini and Vitiello (Nóema, 2012)
the problem of distance the way it is dealt with in the theoretical reflection of Sini and Vitiello, analyzed under three different perspectives: distance as constitutive element of the bodily experience; the human distance of myth, language, writing, mathematics and distance as a hermeneutic problem.
Keywords: Sini; Vitiello; philosophy; ermeneutics; theoretical; sign; interpretant; topology; experience; ethics